Collagen type IV‐related nephropathies in Portugal: pathogenic COL4A5 mutations and clinical characterization of 22 families. (10th November 2014) - Nabais Sá, M.J.; Sampaio, S.; Oliveira, A.; Alves, S.; Moura, C.P.; Silva, S.E.; Castro, R.; Araújo, J.A.; Rodrigues, M.; Neves, F.; Seabra, J.; Soares, C.; et al.
<x xml:space="preserve">Abstract</x> Alport syndrome (AS) is caused by pathogenic mutations in the genes encoding α3, α4 or α5 chains of collagen IV (COL4A3/COL4A4/COL4A5), resulting in hematuria, chronic renal failure (CRF), sensorineural hearing loss (SNHL) and ocular abnormalities. Mutations in the X‐linked COL4A5 gene have been identified in 85% of the families (XLAS). In this study, 22 of 60 probands (37%) of unrelated Portuguese families, with clinical diagnosis of AS and no evidence of autosomal inheritance, had pathogenic COL4A5 mutations detected by Sanger sequencing and/or multiplex‐ligation probe amplification, of which 12 (57%) are novel. Males had more severe and earlier renal and extrarenal complications, but microscopic hematuria was a constant finding irrespective of gender. Nonsense and splice site mutations, as well as small and large deletions, were associated with younger age of onset of SNHL in males, and with higher risk of CRF and SNHL in females. Pathogenic COL4A3 or COL4A4 mutations were subsequently identified in more than half of the families without a pathogenic mutation in COL4A5. The lower than expected prevalence of XLAS in Portuguese families warrants the use of next‐generation sequencing for simultaneous COL4A3/COL4A4/COL4A5 analysis, as first‐tier approach to the genetic diagnosis of collagen type IV‐related nephropathies.